MT-ATP6 9035T>C Variant Causes Ataxia With Azoospermia and Apparent Anticipation in a Four-generation Kindred - Changrui Xiao; David Zhu; Jon Pryor; Sally A. Frutiger; H. Brent Clark; Hannah L. Casey; Matthew Bower; Guo-yun Yu; Xiaofei Du; Camilo Toro; Christopher M. Gomez (The Cerebellum, 2026)
Background The hereditary cerebellar ataxias are a clinically and genetically heterogeneous group of disorders characterized by progressive cerebellar degeneration leading to incoordination of gait, speech, limb, and eye movements. Hundreds of genes encoding diverse proteins underlie this family of degenerative disorders that may exhibit autosomal dominant, recessive, mitochondrial, or X-linked inheritance. Variations in clinical presentation, such as age of onset and severity, are typical of these disorders and are attributed to other genetic effects, notably repeat expansion instability. Methods In this observational study, we evaluated 45 individuals in a 5-generation kindred exhibiting features of progressive ataxia and cognitive impairment with wide-ranging ages of onset, intergenerational anticipation, diverse clinical features, and male infertility. Results The variant (m.9035 T > C) in the gene MT-ATP6 was detected in all affected individuals, and the age of onset from early childhood to the 8th decade was inversely correlated with heteroplasmy levels. Neuropsychological evaluation of affected individuals demonstrated low average/borderline overall intellectual ability and weaknesses in working memory, executive function, memory, and fine motor skills. Affected males had testicular atrophy and azoospermia. Postmortem examination revealed widespread cerebellar Purkinje cell loss. Testicular biopsy from one sterile male demonstrated a complete absence of germ cells and progenitors. Discussion This study expands the phenotypic spectrum of MT-ATP6 to include azoospermia in affected males with cerebellar ataxia. Those with low levels of heteroplasmy had mild adult-onset ataxia reminiscent of many forms of SCA. Those with high levels of heteroplasmy had early onset and suffered from the full complement of ataxia, mild cognitive impairment, and in males’ azoospermia.

The molten salt tritium transport experiment: A pumped fluoride salt loop for hydrogen isotope experimentation - Thomas F. Fuerst; Anthony G. Bowers; Hanns A. Gietl; Nicole L. France; L.Shayne Loftus; Adriaan A. Riet; Matthew D. Eklund; Chase N. Taylor; Masashi Shimada (Annals of Nuclear Energy, 2025)

Host plant‐mediation of viral transmission and its consequences for a native butterfly - Tara Christensen; Lee A. Dyer; Matthew L. Forister; M. Deane Bowers; Adrian Carper; Mike B. Teglas; Paul Hurtado; Angela M. Smilanich (Ecology, 2024)
Pathogens play a key role in insect population dynamics, contributing to short‐term fluctuations in abundance as well as long‐term demographic trends. Two key factors that influence the effects of entomopathogens on herbivorous insect populations are modes of pathogen transmission and larval host plants. In this study, we examined tritrophic interactions between a sequestering specialist lepidopteran, Euphydryas phaeton , and a viral pathogen, Junonia coenia densovirus, on its native host plant, Chelone glabra , and a novel host plant, Plantago lanceolata , to explore whether host plant mediates viral transmission, survival, and viral loads. A two‐factor factorial experiment was conducted in the laboratory with natal larval clusters randomly assigned to either the native or novel host plant and crossed with either uninoculated controls or viral inoculation (20% of individuals in the cluster inoculated). Diapausing clusters were overwintered in the laboratory and checked weekly for mortality. At the end of diapause, all surviving individuals were reared to adulthood to estimate survivorship. All individuals were screened to quantify viral loads, and estimate horizontal transmission postmortem. To test for vertical transmission, adults were mated, and the progeny were screened for viral presence. Within virus‐treated groups, we found evidence for both horizontal and vertical transmission. Larval clusters reared on the native host plant had slightly higher horizontal transmission. Survival probability was lower in clusters feeding on the native host plant, with inoculated groups reared on the native host plant experiencing complete mortality. Viral loads did not differ by the host plant, although viral loads decreased with increased sequestration of secondary compounds on both host plants. Our results indicate that the use of a novel host plant may confer fitness benefits in terms of survival and reduced viral transmission when larvae feeding on it are infected with this pathogen, supporting hypotheses of potential evolutionary advantages of a host range expansion in the context of tritrophic interactions.

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Correction to: Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy - Matthew M. Bower; Shuichi Suzuki; Kiarash Golshani; Li-Mei Lin; Mohammad Shafie; Hermelinda G. Abcede; Jay Shah; Dana Stradling; Wengui Yu (Translational Stroke Research, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy - Matthew M. Bower; Shuichi Suzuki; Kiarash Golshani; Li-Mei Lin; Mohammad Shafie; Hermelinda G. Abcede; Jay Shah; Dana Stradling; Wengui Yu (Translational Stroke Research, 2022)
Cerebral reperfusion injury is the major complication of mechanical thrombectomy (MT) for acute ischemic stroke (AIS). Contrast extravasation (CE) and intracranial hemorrhage (ICH) are the key radiographical features of cerebral reperfusion injury. The aim of this study was to investigate CE and ICH after MT in the anterior and posterior circulation, and their effect on functional outcome. This is a retrospective study of all consecutive patients who were treated with MT for AIS at University of California Irvine Medical Center between January 1, 2014, and December 31, 2017. Patient characteristics, clinical features, procedural variables, contrast extravasation, ICH, and outcomes after MT were analyzed. A total of 131 patients with anterior circulation (AC) stroke and 25 patients with posterior circulation (PC) stroke underwent MT during the study period. There was no statistically significant difference in admission NIHSS score, blood pressure, rate of receiving intravenous tPA, procedural variables, contrast extravasation, and symptomatic ICH between the 2 groups. Patients with PC stroke had a similar rate of favorable outcome (mRS 0–2) but significantly higher mortality (40.0% vs. 10.7%, p < 0.01) than patients with AC stroke. Multivariate regression analysis identified initial NIHSS score (OR 1.1, CI 1.0–1.2, p = 0.01), number of passes with stent retriever (OR 2.1, CI 1.3–3.6, p < 0.01), and PC stroke (OR 9.3, CI 2.5–35.1, p < 0.01) as independent risk factors for death. There was no significant difference in functional outcomes between patients with and without evidence of cerebral reperfusion injury after MT. We demonstrated that AC and PC stroke had similar rates of cerebral reperfusion injury and favorable outcome after MT. Cerebral reperfusion injury is not a significant independent risk factor for poor functional outcome.

What can seabirds tell us about the tide? - Matthew Cooper; Charles Bishop; Matthew Lewis; David Bowers; Mark Bolton; Ellie Owen; Stephen Dodd (Ocean Science, 2018)
Small global positioning system (GPS) trackers are now routinely used to study the movement and behaviour of birds at sea. If the birds rest on the water they become “drifters of opportunity” and can be used to give information about surface currents. In this paper, we use a small data set from satellite-tracked razorbills (Alca torda) in the Irish Sea to test the potential of this idea for measuring tidal currents. Razorbills regularly rest on the sea overnight and their tracks at this time are consistent with their drifting with the tidal flows and changing direction as the flood turns to ebb and vice versa. Data from 4 years (2011–2014) have been binned in a geographical grid and analysed to give the variation of current over a mean tidal cycle in each grid element. A map of maximum current speed is consistent with a numerical model of the tidal currents in the region. The root mean square difference between observed maximum speed and that predicted by the model is 0.15 m s−1, about 15 % of typical current speeds in the area. The divergence between bird-track speed and model prediction increases in regions of the fastest tidal currents. The method clearly has its limitations, but the results of this study show that tagged birds resting on the sea have potential to provide relatively inexpensive quantitative information about surface tidal currents over an extended geographical area.

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

The Expanding Role of Ocean Color and Optics in the Changing Field of Operational Oceanography - Scott Glenn; Oscar Schofield; Tommy Dickey; Robert Chant; Josh Kohut; Hervé Barrier; Jennifer Bosch; Louis Bowers; Elizabeth Creed; Chip Haldeman; Eli Hunter; John Kerfoot; et al. (Oceanography, 2004)